Pendampingan Perencanaan Bangunan Gedung Masjid Al-Awwabin Kelurahan Karang Balik Kota Tarakan - Edy Utomo; Zulfikhar Ade Mahendra; Giar Tri Haryanti (UNIB Press, 2021)
Al-Awwabin Mosque is a mosque built in 1967. Currently the condition of the building is no longer able to accommodate pilgrims. Based on this, the mosque administrator took the initiative to build a new mosque, with a more adequate capacity. However, the mosque administrator experienced some obstacles in planning process of the mosque, including 1. Complexity of land topography problems, 2. Form of architectural design, structure, and preparation of the necessary budget plan, 3. The absence of human resources that have adequate competence in building planning. Based on this, the PKM team from the Department of Civil Engineering, University of Borneo Tarakan strives to make a scientific contribution in the planning of the mosque building, which aims to produce a mosque design with adequate capacity and has architectural value and structural strength in accordance with applicable standardization. The method is initiated by mapping the land, soil investigation (CPT), making preliminary architectural designs, analyzing building structures, making detailed drawings of building construction, and finally calculating the value of the required cost budget plan. The results of this activity is to provide an alternative design with a capacity of 659 worshippers, greater than the capacity of the mosque today. The resulting design of the new mosque consists of 3 floors of the building, where the 1st floor serves as a vehicle parking area and secretariat office, the 2nd and 3rd floors function as the main worship space. The construction of the mosque uses reinforced concrete material with a deep foundation that is Strouss Pile at a depth of 13,00 meters. The estimated value of the cost budget plan is Rp. 10.735.848.000,- based on the basic price of employment and material wages in the Tarakan City area. All design documents consisting of detail drawings, structure design, and DED are submitted to the mosque administrator, which will further serve for the management of building permits as well as references in the implementation of mosque construction. Keywords : Design of the mosque; Community service; Structure of the building; Civil engineering.